Amino acids and proteomic acclimation of Staphylococcus aureus when incubated in a defined minimal medium supplemented with 5% sodium chloride. Issue 6 (9th February 2019) - Alreshidi, Mousa M.; Dunstan, R. Hugh; Macdonald, Margaret M.; Smith, Nathan D.; Gottfries, Johan; Roberts, Tim K.
Abstract: Staphylococcus aureus is a versatile bacterium that can adapt to survive and grow in a wide range of salt concentrations. This study investigated whether the cells could mount a response to survive a challenge of 5% NaCl in a minimal incubation medium that would not support cell replication. Cells were grown in liquid culture, washed and then incubated for 90 min at 37°C in a medium that contained only glycine and glucose as substrates in PBS plus trace elements. The control cells were compared with a treatment group which was incubated with an additional 5% NaCl. Significantly more glycine was taken up by the cells exposed to 5% NaCl compared with control cells, and both groups consumed 99% of the glucose supplied. The NaCl treated cells had significantly higher cytoplasmic levels of proline and glutamic acid as well as lower levels of alanine and methionine compared with the controls ( p  < 0.05). The levels of the two major cytoplasmic amino acids, aspartic acid and glycine, remained constant in control and treated cells. Proteomic analyses revealed that 10 proteins showed differential responses between the control and treatment groups. The reductions in proteins were primarily associated with processes of protein biosynthesis, pathogenicity, and cell adhesion. Since cell numbers remained constant during the incubation period in minimal medium, it was concluded that there was no cell division to support population growth. The results provided evidence that the cells in the minimal medium exposed to the NaCl treatment underwent in situ homeostatic changes to adjust to the new environmental conditions. It was proposed that this represented a phenotypic shift to form cells akin to small colony variants, with lower metabolic rates and lower levels of key proteins associated with pathogenicity. Abstract : Metabolomic and proteomic investigations showed that Staphylococcus aureus adapted to osmotic stress by inducing significant alterations in the metabolites and proteins. These alterations were thought to provide the survival mechanism to undesirable conditions.